A Study on the Sex Ratio of Mizo In Mizoram: Exploring the Sex Ratio of Mizo in Mizoram: Causes, Trends, and Predictions (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The paper examines the sex ratio of Mizoram and Mizo in Mizoram since1911 and also traced the causes of sex ratio reversal in 1971. The paperemployed the SPSS package for analyzing the data and fitted the cubic model ofregression for prediction of the sex ratio. The paper concluded that there are more female member than male amongthe Mizo tribe and predicts that the sex ratio of Mizoram will be 105.62 in2021 census.